The Sparks of the Phonograph, Echoes of Revolution: Béla Bartók and the Birth of Modern Ethnomusicology as a Scholarly Discipline - Rahmat Kurniawan; Sri Riski Wulandari (Surakarta: Jurusan Karawitan Institut Seni Indonesia Surakarta, 2026)
Folk music in nineteenth-century Europe was frequently perceived in a romanticized manner as a symbol of national identity, thereby obscuring a scholarly understanding of its authentic traditions. This article aims to examine the central role of Béla Bartók in establishing the foundational principles of modern ethnomusicology, with particular focus on his use of the phonograph as a revolutionary instrument in folk music research. The study employs a qualitative approach grounded in historical and descriptive-analytical literature review, synthesizing Bartók's own primary writings with secondary sources drawn from a range of academic musicological studies. The findings demonstrate that the phonograph enabled Bartók to conduct objective field recordings, execute microscopically precise transcriptions, and systematically classify melodic materials, while simultaneously correcting prevalent misconceptions between authentic Hungarian peasant music and the so-called style hongrois. Bartók's ethnomusicological discoveries not only forged a new scientific methodology for the cross-cultural study of music, but also fundamentally transformed his compositional practice through an organic synthesis of folkloric elements and twentieth-century modernism. The study concludes that Bartók's contributions marked a fundamental paradigm shift in the way the world perceived folk music from an object of romanticization to a subject of rigorous scholarly inquiry leaving a methodological legacy that remains relevant to contemporary ethnomusicology